Technology transformations in research evaluation metrics data: library reference services and research intelligence in China - Qiu, Lulu; Zhou, Elsie; Yu, Tiffany; Smyth, Neil (2018)
Technology transformations in research data metrics are challenging librarians to re-position in the evolving cycles of research production, communication and evaluation. This paper focuses on a new reference and information service for research data analytics that was launched in 2017, including new needs and new skills in strategic research intelligence. Librarians are challenged by the new and emerging strategic needs of universities for data-driven research intelligence that provides a comparative edge in the global world of higher education. Leading universities need research data to analyse the performance at multiple levels, including: the individual researcher, establishing clear expectations for career progression; research groups and clusters, collating researchers together to identify and communicate outstanding areas of research excellence; and, at the institutional level, to make national and international comparisons against other leading institutions around the world. They need to know and apply international assessment standards. They need libraries to deliver new reference and information services based on data analytics. Technology transformations in research data metrics are enabling librarians to develop the new skills and a new position in the evolving cycles of research production, communication and evaluation. Publishers increasingly control the scholarly infrastructure. This provides both the challenge and opportunity for librarians to develop new roles in data evaluation metrics: facilitating digital literacy in emerging areas, such as Using Google Scholar institutional level data to evaluate the quality of university research; delivering expertise in research technology tools for data, such as SciVal; and, communicating through data visualisation of research evaluation data and the analysis of data in research intelligence reports and presentations. This paper focuses on a new reference and information service in China for research data analytics that was launched in 2017. There is a discussion of how new university needs have provided the strategic drive for librarians to develop skills. These skills include data extraction, analysis and visualisation, building on traditional librarian strengths and expertise. This has driven the development of the library's position and influence in strategic research intelligence services. The project and service development is significant for showcasing a new role for librarians in relation to research data evaluation metrics linked to publication strategies for authors and strategic intelligence for institutions.